2013
DOI: 10.1148/radiol.12120134
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Radiation Dose at CT Colonography: Decreasing Tube Voltage to 100 kVp

Abstract: Purpose:To assess the effect of a decrease in tube voltage from 120 kVp to 100 kVp on dose, contrast-to-noise ratio (CNR), and three-dimensional (3D) image quality in patients undergoing computed tomographic (CT) colonography as well as to determine how these changes are affected by patient size. Materials and Methods:This HIPAA-compliant and institutional review board-approved retrospective study included 63 consecutive patients who underwent CT colonography and who waived informed consent. Scanning was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Chang et al (7) who first assessed the effect of low tube voltage on the image quality at CTC demonstrated that the 100-kVp CTC protocol with FBP allowed for a reduction in CTDI vol by 20% and of DLP by 16%. However, their study showed a decrease in the 3D image quality and did not include IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al (7) who first assessed the effect of low tube voltage on the image quality at CTC demonstrated that the 100-kVp CTC protocol with FBP allowed for a reduction in CTDI vol by 20% and of DLP by 16%. However, their study showed a decrease in the 3D image quality and did not include IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased image noise, a byproduct of low-tube-voltage settings, is a serious problem (6). Chang et al (7) assessed the effect of lowtube-voltage techniques on the image quality of CTC in 63 patients. They found that a decrease in the tube voltage from 120 to 100 kVp with filtered back projection (FBP) resulted in a significant decrease in the radiation dose and a decrease in the three-dimensional (3D) image quality.…”
mentioning
confidence: 99%
“…13 Our initial attempts to use low-energy scanning at 100 kV peak tube voltage that may otherwise be used to decrease the radiation dose by 20% were discouraging, because in a submillisievert region, it contributed to increased image noise to a greater extent than what could be compensated by increasing the tube current while maintaining low radiation dose. 8,14 A 140-kV protocol used with a 10-mAs time-current product and FBP results in a 1.8-to 2.4-mSv radiation dose and ensures excellent sensitivity for detection of relevant ($6 mm) lesions. 6 However, in our specific scanner, the reference timecurrent product cannot be set to ,10 mAs and therefore the 140-kV protocol was not used.…”
Section: Discussionmentioning
confidence: 99%
“…4 Further reduction of the radiation dose while maintaining diagnostic acceptability requires special considerations regarding acquisition and image-processing techniques. [7][8][9] In particular, new developments in the field of iterative reconstruction offer further reduction of the radiation dose with preserved image quality. 7,10 The objective of this study was to compare image quality of different reconstruction techniques in a submillisievert ultralow-dose CTC in order to assess image quality and recommend the most applicable technique.…”
mentioning
confidence: 99%
“…In addition, at a lower tube potential, the average energy of the X-ray beam more closely approaches the K-edge of iodine leading to an increase in attenuation of iodinated contrast medium. 20 The use of a lower tube potential to reduce radiation dose and increase the contrast medium attenuation of tagged colonic fluid has already been demonstrated in CTC 21 as well as multiple other contrast-enhanced applications 17,22e28 ; however, in one study, the decrease in tube potential from 120 to 100 kVp resulted in a 32% increase in image noise. 21 Iterative reconstruction methods such as adaptive statistical iterative reconstruction (ASiR, GE Healthcare, Waukesha, WI, USA) use an alternative method of reconstructing CT data that reduces image noise while preserving edge detail 29,30 when compared to filtered back projection.…”
Section: Introductionmentioning
confidence: 99%